2015
DOI: 10.1093/hmg/ddv621
|View full text |Cite
|
Sign up to set email alerts
|

Wnt4 coordinates directional cell migration and extension of the Müllerian duct essential for ontogenesis of the female reproductive tract

Abstract: The Müllerian duct (MD) is the anlage of the oviduct, uterus and upper part of the vagina, the main parts of the female reproductive tract. Several wingless-type mouse mammary tumor virus (MMTV) integration site family member (Wnt) genes, including Wnt4, Wnt5a and Wnt7a, are involved in the development of MD and its derivatives, with Wnt4 particularly critical, since the MD fails to develop in its absence. We use, here, Wnt4EGFPCre-based fate mapping to demonstrate that the MD tip cells and the subsequent MD c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 39 publications
2
61
0
1
Order By: Relevance
“…The wnt4a expression domain anterior to the eventual connection of the FDD and the genital orifice supports the hypothesis that tissues around the genital orifice likely secretes Wnt4a protein, and thus signal duct growth, elongation and connection to the exterior. Thus, as in mammals, Wnt4a may coodinate directional cell migration and extention of the reproductive duct (Prunskaite-Hyyryläinen et al . 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The wnt4a expression domain anterior to the eventual connection of the FDD and the genital orifice supports the hypothesis that tissues around the genital orifice likely secretes Wnt4a protein, and thus signal duct growth, elongation and connection to the exterior. Thus, as in mammals, Wnt4a may coodinate directional cell migration and extention of the reproductive duct (Prunskaite-Hyyryläinen et al . 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The recent findings demonstrated that the morphological changes leading to a less coiled or uncoiled oviduct and formation of cysts within the oviduct can result in infertility. Wingless-type integration family member 4 (WNT4) signaling is critical for the development of the female reproductive tract, as female mice lacking Wnt4 expression showed a non-coiled oviduct that lacked folding (Prunskaite-Hyyrylainen et al 2016). Moreover, overexpression of Notch in the reproductive tract produced similar phenotypes whereby the oviduct failed to coil (Ferguson et al 2016).…”
Section: Pathways Crucial For Normal Oviduct Developmentmentioning
confidence: 99%
“…This process involves a close interaction between epithelial cells and underlying mesenchyme (Figures 2 and 3). Important players in duct formation include the homeodomain transcription factors, EMX2, HOXA13, PAX2, and LIM1, and members of the Wnt family of secreted growth factors (namely, WNT4, WNT9B, and WNT7A) (Bouchard, Souabni, Mandler, Neubuser, & Busslinger, 2002;Kobayashi & Behringer, 2003;Kobayashi, Shawlot, Kania, & Behringer, 2004;Prunskaite-Hyyrylainen et al, 2016;Torres, Gomez-Pardo, Dressler, & Gruss, 1995) ( Figure 3). Although required for MD elongation, the first phases of development (specification and invagination) are thought to be independent of the WD (Carroll et al, 2005;Mullen & Behringer, 2014).…”
Section: Genetic Regulation Of MD Formationmentioning
confidence: 99%